Ü-Life it's all about you in U - Evangelio, Dianne Bernadette; Hari, Mia Melanie; Moreno, Ma. Victoria; Panes, Trisha Marie (College of Engineering, University of the Philippines Diliman, 2009)
This study is a development of a project feasibility of putting Ü-life, an online directory of rental residences, part-time job listings, and student organizations that is specifically designed to cater a growing need in the UP Diliman community. With only half of the expected number of dorm residency applications (from the freshmen population alone) being approved each year, the need for a handy and easily accessible information database is becoming more and more necessitated. Addition of other auxiliary student services information (Job-listings, student org updates, etc.) widens the project's market scope. This is further demonstrated by the 86% approval rate from the 200 randomly selected UP students. The number of internet users in the Philippines has doubled in 2008 since the nearly 8 million users in 2005. This number continues to grow at a recorded rate of 28% in the last quarter of 2008. While the Philippines is still among those that has the weakest internet support in South East Asia, the growing reliance of students on website resources is very much apparent especially in the urban areas. Moreover, popularity of online advertisement proves to equally progress through this trend. The Mobile Marketing Association of the Philippines estimated Php 100 Million revenues from internet ads with each advertising site earning P500,000 yearly on the average. Ü-life's information system structure, business processes, and other support operations designed and developed in the technical section are found feasible and most effective in its current blueprint. A website prototype is also made available to partially test usability. The project's total start-up cost is P 349, 658.35. This includes all fixed assets, initial costs, and allowances for a 5-month working capital. Projected annual revenue at the end of year 5 is P 439,824. 76. With a forecasted ads sales of P590, 400 in year 1, break-even is achieved before the end of its first year. Sales is expected to stabilize at the beginning of year 3 when maximum add pages available are all filled. With expenses kept at minimum an IRR of 48.42% is established. Originally formulated to be of service to the UP community, establishment of Ü-life best promotes the social-economic and financial viability. It evens out and redistributes the resources from coming from high-earning companies for the benefit of the community. Overall feasibility is achiev